2020
DOI: 10.1002/lno.11632
|View full text |Cite
|
Sign up to set email alerts
|

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation

Abstract: Cross-shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross-shore transport in the shallow ($ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini-Autonomous Underwater Explorers (M-AUEs). The M-AUEs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have shown that the inclusion of larval behaviors alter dispersal pathways (Faillettaz et al, 2018; Levin, 2006; Rypina et al, 2014). This is most notable for larvae that exhibit vertical movements in areas with high vertical velocity shear (Garwood et al, 2021; Tapia & Pineda, 2007). The Gulf of Maine in winter is well mixed and thus vertical velocity shears are low on banks for much of the larval duration of sand lance (Mountain & Manning, 1994), though waters begin to stratify in the spring and thus vertical gradients in velocity begin to increase as sand lance larvae approach settlement (Mountain & Manning, 1994; Naimie et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the inclusion of larval behaviors alter dispersal pathways (Faillettaz et al, 2018; Levin, 2006; Rypina et al, 2014). This is most notable for larvae that exhibit vertical movements in areas with high vertical velocity shear (Garwood et al, 2021; Tapia & Pineda, 2007). The Gulf of Maine in winter is well mixed and thus vertical velocity shears are low on banks for much of the larval duration of sand lance (Mountain & Manning, 1994), though waters begin to stratify in the spring and thus vertical gradients in velocity begin to increase as sand lance larvae approach settlement (Mountain & Manning, 1994; Naimie et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…To properly represent water particle motions, the velocity used at each time step should be that appropriate to the particle's location at any time. Observationally, this would mean that either one deploys many instruments (as did Gaylord et al., 2007), or one should track Lagrangian particle displacements with neutrally buoyant drifters (e.g., Garwood et al., 2021). Nonetheless, we argue that our estimates of ζ $\zeta $ and T r based on data from a single ADP are sufficient to show the effects of the presence or absence of kelp.…”
Section: Discussionmentioning
confidence: 99%